Effect of Qualea multiflora on macrophages and tumour cells - Carli, Camila B. de A. [UNESP]; Quilles, Marcela B. [UNESP]; Vilegas, Wagner [UNESP]; Carlos, Iracilda Z. [UNESP] (My University, 2013)
Species of the genus Qualea are used by the Brazilian people as a natural anti-inflammatory. Based on this evidence, we evaluated the effects of terpene fractions βF and TF (rich in β-sitosterol and terpenoids, respectively) obtained from Qualea multiflora on nitric oxide production, cytokines (IL-1, IL- 10, IL-12, and TNF-α) and the transcription factor NF-κB by peritoneal macrophages. Since there is a relationship between inflammation and cancer, the cytotoxicity of βF and TF against mammary and pulmonary tumoural cell lineages, and macrophages was evaluated. Inhibition levels close to 90% of the production of NO, IL-1, IL-12 and TNF-α; about 32% of NF-κB; and a large stimulation of IL-10 production (close to the positive control) by peritoneal macrophages were observed in response to βF and TF which are correlated with anti-inflammatory activity. Additionally, the samples showed cytotoxic activity against tumoural cells but not against macrophages. Since anti-inflammatory activity is important in tumour inhibition, further examination of potential anti-cancerous activity of Qualea multiflora is warranted.
Keywords: Cancer; Macrophages; Qualea multiflora